The Effect of Teachers’ Creative Models on Students' HOTS in Digital Mathematics Learning - Zamzam, Kenys Fadhilah; Anugraini, Asri Putri; Susandi, Susandi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Developing higher-order thinking skills (HOTS) in mathematics education remains a challenge, particularly regarding the use of technology, which often serves merely as a medium for delivering content without innovation in task design. Unlike previous studies that focused on the use of technology or instructional models, this study positions teachers’ creativity in designing digital tasks as the primary factor influencing HOTS and student engagement. This study aims to analyze the influence of teachers’ creative models on HOTS skills and the engagement of junior high school students. The study employs a quantitative approach with a quasi-experimental design involving 120 students. Teachers’ creative models were identified through analysis of digital assigments products and classroom observations, then classified based on indicators of context, problem-solving procedures, and assignment structure in digital format into four levels: imitation, transition, modification, and construction. Data were collected through HOTS tests and student engagement questionnaires, then analyzed using ANOVA. The results showed that there were significant differences in students’ HOTS abilities and engagement based on the level of the teacher’s creative model. Students at the modification and construction levels demonstrated higher results. These findings confirm that the quality of creative digital assignment design is key to enhancing technology-based mathematics learning.